The A REVIEW ON CASING WHILE DRILLING (CWD) TECHNOLOGY FOR OIL AND GAS PRODUCTION (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The extraction of petroleum fluids from sub-surface accumulations mandates the drilling of a well into the formation containing the accumulation. The drilling techniques have evolved over time to overcome several challenges while some of the issues still prevail with the currently used drilling practices like loss circulation, large tripping time to change bottom hole assembly, stuck pipe problems and low well bore stability, to name a few. These decrease the drilling efficiency and increase the Non-Productive Time (NPT) of this highly capitalintensive industry encouraging the Petroleum Industry to look for new technology. Casing while Drilling (CwD) is a technique of drilling which has been proven to alleviate many of the problems faced while drilling. It has proven to be beneficial in controlling loss circulation and improving wellbore stability by ‘Plastering’ effect, high quality cement job and increased rig floor safety. It uses smaller rig and less fuel thereby reducing carbon footprint in the environment. This paper reviews casing while drilling (CwD) technology for oil and gas production. Categories, components, accessories and challenges of CwD are discussed in this paper